PERSEPSI MASYARAKAT TERHADAP KEDISIPLIN APARATUR SIPIL NEGARA DI KANTOR CAMAT TAMPAN KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a phenomenon that appears based on pre-research conducted by researchers in accordance with the reality that occurs in the field which shows that there are still state civil servants who have not implemented discipline in the handsome sub-district office of Pekanbaru City. Based on Government Regulation no. 53 of 2010 article 1 that Civil Servant Discipline is the ability of Civil Servants to comply with obligations and avoid the prohibitions stipulated in statutory regulations and / or official regulations which if not obeyed or violated are subject to disciplinary punishment and disciplinary violation is every word, writing, or acts of civil servants who do not comply with their obligations and / or violate the prohibitions on civil servant discipline provisions, both inside and outside working hours. The formulation of the problem in this study is What is the Community's Perception of the Discipline of the State Civil Apparatus in the Tampan Sub-District Office, Pekanbaru City? This study aims to determine how the community's perceptions of the discipline of employees of the Tampan sub-district office in Pekanbaru City. This research method is a questionnaire, observation, interview and documentation. The population in this study was the handsome sub-district community, amounting to 194,331 people. The sample in this study amounted to 20 people. Based on the results of the study, it was found that the average percentage value of the alternative answers to the dominant respondents was 82.7%, where this range is in the